2020
DOI: 10.1177/2309499020936005
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcome of severe rigid idiopathic scoliosis: Single-staged posterior spinal fusion utilizing a dual attending surgeon strategy. A report of 41 patients

Abstract: Purpose: Various surgical strategies including combined approach and spinal osteotomies in severe rigid scoliosis had been reported with significant perioperative complication rates. The use of single-staged posterior spinal fusion (PSF) utilizing a dual attending surgeon strategy for severe rigid scoliosis has not been widely reported. Methods: This was a retrospective study aimed to evaluate the perioperative outcome of single-staged PSF in severe rigid idiopathic scoliosis patients (Cobb angle ≥90° and ≤30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…A total of 1337 studies were found through electronic search; after screening, 14 studies (1 prospective cohort study,[ 23 ] 3 retrospective comparative studies,[ 24 25 26 ] 1 retrospective cohort study,[ 27 ] 6 retrospective studies,[ 28 29 30 31 32 33 ] 1 prospective CS,[ 34 ] and 2 retrospective CS[ 1 21 ]) were included. [ 1 21 23 24 25 26 27 28 30 31 33 34 ] The quality of the papers was good in 13 cases[ 1 21 23 24 25 26 27 28 30 31 33 ] and fair in 1 case. [ 34 ]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 1337 studies were found through electronic search; after screening, 14 studies (1 prospective cohort study,[ 23 ] 3 retrospective comparative studies,[ 24 25 26 ] 1 retrospective cohort study,[ 27 ] 6 retrospective studies,[ 28 29 30 31 32 33 ] 1 prospective CS,[ 34 ] and 2 retrospective CS[ 1 21 ]) were included. [ 1 21 23 24 25 26 27 28 30 31 33 34 ] The quality of the papers was good in 13 cases[ 1 21 23 24 25 26 27 28 30 31 33 ] and fair in 1 case. [ 34 ]…”
Section: Resultsmentioning
confidence: 99%
“…The included studies chose different criteria for the definition of severe scoliosis: Seven authors used a major curve Cobb >90° as a cutoff[ 24 27 28 30 31 32 33 ] (1 of them[ 30 ] used major curve Cobb >90° and flexibility index <30%), 4 used a major curve Cobb >80°[ 1 21 25 34 ] (2 of them[ 1 34 ] used major curve Cobb >80° and flexibility index <25%), 3 used a major curve Cobb >70°[ 23 26 35 ] [ Table 1 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations